Migration attitudes and mechanisms for attracting young people to the Russian Arctic - Eduard Z. Galimullin (Арктика и Север, 2019)
In this article, the author considers the migration outflow of the population from the Russian Arc-tic, a significant part of which are representatives of the socially active youth. A study of young people's motivations to move to a permanent or temporary place of residence in the Arctic showed that the idea of a region dominates the consciousness of this social group, characterized more by negative associations, such as “ice”, “cold” and “snow”. Nevertheless, some specific material incentives that, according to respondents, would positively influence a possible decision to relocate revealed. We are talking about providing additional paid vacations and rental housing. It was also possible to establish approximate boundaries of the minimum wage enough to decide on moving. The author claims that the socio-economic conditions changed after the collapse of the USSR. The state labor policy in the Arctic requires clarification concerning the discussed development options. Also, it demands the coherence of all measures taken at the legislative level in the context of speedy adoption of the fundamental law on the Russian Arctic. It is necessary to continue the policy of supporting various volunteer organizations as the most active and mobile structures for informing young people about employment opportunities in the Arctic and involving their representatives in socially useful activities.